(untitled) (SAARC Journal of Agriculture, 2023)
Salinity in the most critical abiotic stress particularly in the coastal area of Ganges Delta. The cropping in the coastal regions of southwestern (SW) Bangladesh during Boro season mainly constraint by the soil and water salinity. Therefore, responses of the rice to different degree of salinity is important. So, a pot experiment was conducted at Dr. Purnendu Gain Field Laboratory of Agrotechnology Discipline, Khulna University, Khulna to screen the response of 8 different boro rice varieties (Noyanmoni, Abdulhai, Kaliboro, BRRI dhan55, Noyantara, Kajollota, Bareyratna, BINA dhan8) at different levels of salinity (0, 4, 8, 12, 16 and 20 dS m-1). The experiment was conducted in a factorial completely randomized deign and replicated thrice. All the growth, yield attributes and yield were significantly declined with the increased levels of salinity compared to control (no salt solution added). All the plants were died with the imposed salinity levels at 12, 16 and 20 dS m-1. Therefore, the collected parameters of rice varieties at 0-8 dS m-1 salinity levels were analyzed. Rice varieties respond well up to 4 dS m-1 and afterwards poor response noticed. Noyanmoni showed best performance in terms of growth, yield attributes and yield compared to other varieties in salinity conditions. From the findings of this study, it is concluded that under medium saline condition Noyanmoni is the suitable rice variety and can be fitted in the coastal saline soil of southwestern Bangladesh during Boro season. SAARC J. Agric., 21(1): 127-137 (2023)